Prognostic Value of Neutrophils-to-Lymphocytes Ratio and Platelets-to-Lymphocytes Ratio in Sepsis Patients With Lymphopenia - Xianming Qiu; Quanzhen Wang; Yuke Zhang; Qiannan Zhao; Zhiming Jiang; Lei Zhou (Biomarker Insights, 2024)
Background: Inflammation plays a critical role in sepsis. The integration of neutrophil-to-lymphocyte ratio (NLR) and platelets-to-lymphocytes ratio (PLR) from multiple cell types offers a novel approach to rapidly assess inflammation status. However, the predictive role of NLR and PLR in sepsis with lymphopenia remains uncertain. Objectives: The purpose of this study was to explore the prognostic value of NLR and PLR in sepsis patients with lymphopenia. Design and methods: In this observational retrospective study, we included 172 sepsis patients with lymphopenia and collected clinical characteristics for analysis. Through binary logistic regression analysis, we identified independent factors. Receiver-operating characteristic curves (ROC) and areas under the curves (AUC) were employed to assess the ability to predict hospital mortality risk. Results: Our results showed a total hospital mortality rate of 53.49%. Multivariate analysis demonstrated that NLR (OR = 1.11, P  < .001) and PLR (OR = 1.01, P  = .003) were independent predictors associated with hospital mortality in sepsis patients with lymphopenia. The AUCs of NLR and PLR were 0.750 (95% CI: 0.634-0.788, P  < .001) and 0.662 (95% CI: 0.580-0.743, P  < .001), respectively. Notably, an optimal cut-off value of 18.93 for NLR displayed a sensitivity of 75.0% and specificity of 63.0% in discriminating hospital mortality in sepsis patients with lymphopenia, while the optimal cut-off value for PLR was 377.50, with a sensitivity of 67.5% and specificity of 64.1%. Conclusion: NLR and PLR serve as independent predictors of hospital mortality in sepsis patients with lymphopenia.